MENINGKATKAN HASIL BELAJAR IPS MELALUI PENDEKATAN KONTEKSTUAL PADA SISWA KELAS VB SDN BALANG BARU 1 KECAMATAN TAMALATE KOTA MAKASSAR - Irayanti Irayanti; Hamzah Upu; Thamrin Tahir; Muh. Yunus (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
Research problems in this study is the low of learning outcomes of IPS on class VB SDN Balang Baru 1 District Tamalate Makassar City. What if the use of contextual approach can improve student learning outcomes of VB grade SDN Balang Baru 1 District Tamalate Makassar City. The objective of the research is to improve students' learning outcomes through contextual approach of VB SDN Balang Baru 1 sub student Tamalate Kota Makassar. This research is a qualitative research with class of recycled / cycle research, which includes planning, implementation, and reflection. . The focus of research is to improve the learning outcomes of IPS through contextual approach. The subjects of the study were teachers and students of VB SDN Balang Baru 1 sub district Tamalate Kota Makassar. Data information technic is test, test, and documentation. Data analysis techniques are data reduction, data presentation, conclusion and verification. Results of research and improvement of student learning outcomes. The increase can be seen in each cycle, cycle I reaches Enough qualification (C) and in cycle II reaches the Good qualification (B). Writing research using contextual approach can improve student learning outcomes of Fifth B grade SDN Balang Baru 1 District Tamalate Makassar City.